Lutfi Paşa’nın (893/ 1488-972/ 1562) “Halasü’l-Ümme Fi Ma’rifeti’l-Eimmeti” risalesinin tahkik, tahlil ve tercümesi - Jahja, Muharem (My University, 2003)
The issue of Caliphat’s Qureyshi descent has been one of the most discussed/ argued issues as well as one that countless works have been written on, in the Islamic political history. One of these countless works is also Grand vizier Lutfi Pasa’s “Halasu’l Umme fi Ma’rifeti’l-Eimme” (Community’s salvation is based on the knowledge of imams) manuscript risala. By relying on the original sources, Lutfi Pasha in his risala has tried to prove that the Qurayshiness is not a condition for the (Imamat) state presidency. In addition, with examples he has put forward the conditions, responsibilities and the competencies of the person that will step on the Caliphate post or position. In conclusion he has stressed that the epoch’s ruler Sultan Suleyman is also a Caliph. Though having the attention of many researchers, there has not been a critical edition nor a full translation except the partial one of this manuscript. This study makes the critical edition, translation and evaluation of the risala. In the critical edition part, the authors various quotes’ sources and their validity are determined. Whereas in the translation part, the evaluation of existing partial translations’ made by various researchers’, has been done. Halîfenin nesep yolundan Kureys’ten olup olmama sarti, Islâm siyaset tarihinin en çok tartisilan ve hakkinda sayisiz eserler yazilan bir konudur. Bu sayisiz eserlerden biri Sadrâzam Lütfi Pasa’nin “Halâsü’l-Ümme fî Ma’rifeti’l-Eimme” (Ümmetin Kurtulusu Imâmlarin Bilinmesine Baglidir) risalesidir. Lütfi Pasa risalesinde Kureysiligin, Imâmet (Devlet Baskanligi) için sart olmadigini ileri sürerek, dönemin muteber kaynaklarina basvurarak ispatlamaya çalismistir. Ayrica hilâfet makamina oturacak sahis için gereken sartlari, yetkilerini ve görevlerini örneklerle ele almistir. Sonuç olarak, devrin padisahi olan Sultan Süleyman’nin da bir halife oldugunu vurgulamistir. Birçok arastirmacinin ilgisini çeken bu yazma eserin tenkitli metin nesri yapilmamis ve cüz’i tercümeler disinda metnin tamami tercüme edilmemistir. Bu çalismada, risalenin tahkiki, tercümesi ve degerlendirilmesi yapilmistir. Tahkikte ayrica, yazarin farkli kaynaklardan yaptigi aktarmalar tespit edilmis, sihhat derecesine isaret edilmistir. Tercüme bölümünde ise, kimi arastirmacilar tarafindan önceden yapilmis cüz’i tercümelerin degerlendirilmesine de yer verilmistir.
Keywords: Din; İslam; İslam Dini